COMPARATIVE SOCIAL VULNERABILITY ASSESSMENT IN PURBA MEDINIPUR DISTRICT, WEST BENGAL, INDIA - Sumita GAYEN; Luis Ismael VALLEJO VILLALTA; Sk Mafizul HAQUE (European Journal of Geography)
Social vulnerability assessment is an important element for disaster risk reduction system. Social vulnerability depends on physical, social, economic, environmental factors, etc., which determine the susceptibility of community against the impact of hazards. Over the past two decades, social vulnerability has been measured by using different methodologies. The present work portrays a comparative assessment of social vulnerability methodologies in the Purba Medinipur district located in the eastern part of India. Different standardization techniques of data transformation like, Z score, maximum value, and min-max rescaling have been employed to compare and examine social vulnerability in the study area. The principal aim of this work is to analyse the results between the three methodologies adopted, and identify the vulnerable blocks in the district. The result shows that relationships between three methodologies are moderately strong to very strong and Sutahata block is identified as the most vulnerable block in the Purba Medinipur district